Status Perikanan Tangkap di Kabupaten Kebumen - Yahya, Reza; Mahdiana, Arif; Muslih, Muslih (MAIYAH, 2023)
Capture fisheries in Kebumen Regency has a large potential of fish resources. The status of capture fisheries in Kebumen Regency includes the development of the number of fishermen/RTPs, fishing vessels, fishing gear, fishing production volume, fishery production value, types and catches of fish. The results showed that Kebumen fishermen are included in the category of small fishermen based on the use of boat types less than 5 GT and outboard motorboats. The number of growth of fishermen and the number of fishing boats in Kebumen Regency increased throughout 2016-2020. Types of fishing gear used by fishermen in Kebumen district include fixed gill nets, drift gill nets, trammel nets, fishing rods and hooks. The production volume and production value of the Kebumen capture fishery decreased in 2020 due to the COVID-19 pandemic. Potential species caught by Kebumen fishermen were demersal fish with high economic value such as white pomfret (Pampus argenteus), lobster (Panulirus homarus), jerebung shrimp (Penaeus merguiensis) and red snapper (Lutjanus campechanus).